Repere conceptuale în jurisprudența Curții Constituționale a României privind soluționarea conflictelor între ramurile puterii în stat [Articol] - Moldovanu, Radu (CEP USM, 2024)
Acest articol își propune să ofere o analiză a problemelor conceptuale legate de competența Curții Constituționale a României în soluționarea conflictelor instituționale dintre autoritățile politice.Astfel, obiectivul principal este de a analiza abordarea Curții Constituționale a României privind asigurarea principiului separației puterilor.

This article aims to provide an analysis of the conceptual issues related to the Constitutional Court of Romania jurisdiction in solving institutional conflicts between the political authorities.Thus, the main objective is to analyze the Constitutional Court of Romania approach regarding the insurance of the separation of powers principle.
CONCEPTUAL BENCHMARKS IN THE JURISPRUDENCE OF THE CONSTITUTIONAL COURT OF ROMANIA REGARDING THE RESOLUTION OF CONFLICTS BETWEEN THE BRANCHES OF POWER IN THE STAT
Keywords: Curtea Constituțională a României; separarea puterilor în stat; conflicte instituționale între autorități; Constitutional Court of Romania; separation of powers in the State; institutional conflicts between the authorities